2014 International Conference and Workshop on the Network of the Future (NOF) 2014
DOI: 10.1109/nof.2014.7119773
|View full text |Cite
|
Sign up to set email alerts
|

Quality of service and performance evaluation: A fluid approach for poisson wireless networks

Abstract: The evaluation of performance and quality of service needs the modeling of wireless networks. Among the different models usually considered, the hexagonal network is the most popular. However, it requires extensive numerical computations. The Poisson network model, for which the base stations (BS) locations form a stochastic spatial Poisson process, allows to consider a non constant distance between base stations. Therefore, it characterizes more realistically operational networks. The Fluid network model, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…where a = 3 and b = -6, for a wide range of values of η (ranging from 2.2 to 4.2, usual range for the path-loss exponent is comprised between 2.8 and 3.6) We observed that for η = 2.8, 3, 3.6, 3.8, the CDF of the SINR established by the modified Fluid model and by the Poisson model are very close: the differences between them are less than 0.4 dB [17].…”
Section: Comparison Of the Sinr Cdf For The Poisson And Fluid Modelsmentioning
confidence: 71%
See 2 more Smart Citations
“…where a = 3 and b = -6, for a wide range of values of η (ranging from 2.2 to 4.2, usual range for the path-loss exponent is comprised between 2.8 and 3.6) We observed that for η = 2.8, 3, 3.6, 3.8, the CDF of the SINR established by the modified Fluid model and by the Poisson model are very close: the differences between them are less than 0.4 dB [17].…”
Section: Comparison Of the Sinr Cdf For The Poisson And Fluid Modelsmentioning
confidence: 71%
“…In the following section, we remind that we established [17] a correspondence between a stochastic Poisson network and the Fluid network model.…”
Section: B Calculation Of the Sinrmentioning
confidence: 99%
See 1 more Smart Citation
“…We point out that the computational complexity of the model is out of the paper scope, as well as the comparison to the spatial Poisson process. In the latter case, some results can be found in [21].…”
Section: Introductionmentioning
confidence: 84%